PREVENTIVE EFFORTS OF CORRUPTION THROUGH RELIGIOUS MORAL REINFORCEMENT AND REPRESIVE EFFORTS THROUGH THE IMPLEMENTATION OF THE REVERSAL BURDEN PROOF IN ERADICATING CORRUPTION IN INDONESIA - Sulistyowati Sulistyowati (Jurnal Pembaharuan Hukum, 2018)
Corruption in Indonesia occurs systematically and extends not only state finances, but also has increased rights and space for society, but also needs to be done in the normal way. Thus, the eradication of corruption must be done in a special way through moral reinforcement and repressive efforts through the application of reversed proof. One way that can be done to resolve corruption, is to take preventive action as a preventive action and law enforcement action, in a repressive way. The spiritual spiritual service is the guidance, the life to determine the attitude and purpose of life. Religious spirituality as well as a solid foundation for determining the direction of life and as the ideal ideal to guide and direct, every human desire and passion